2018
DOI: 10.1016/j.neuroscience.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Tau Deficiency Down-Regulated Transcription Factor Orthodenticle Homeobox 2 Expression in the Dopaminergic Neurons in Ventral Tegmental Area and Caused No Obvious Motor Deficits in Mice

Abstract: Tau protein participates in microtubule stabilization, axonal transport, and protein trafficking. Loss of normal tau function will exert a negative effect. However, current knowledge on the impact of tau deficiency on the motor behavior and related neurobiological changes is controversial. In this study, we examined motor functions and analyzed several proteins implicated in the maintenance of midbrain dopaminergic (DA) neurons (mDANs) function of adult and aged tau+/+, tau+/−, tau−/− mice. We found tau defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“… Three month old wild-type (WT) and homozygous tau KO (tau-/-) mice were obtained from The Jackson Laboratory (strain name: B6.129-Mapttm1Hnd/J Bar Harbor, ME, Stock no 007251). Tau -/- mice are viable and successful reproducible, and have a normal life-span reaching 20 month-old [26] , [82] . The animals were handled according to the guidelines of the National Institute of Health (NIH, Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%
“… Three month old wild-type (WT) and homozygous tau KO (tau-/-) mice were obtained from The Jackson Laboratory (strain name: B6.129-Mapttm1Hnd/J Bar Harbor, ME, Stock no 007251). Tau -/- mice are viable and successful reproducible, and have a normal life-span reaching 20 month-old [26] , [82] . The animals were handled according to the guidelines of the National Institute of Health (NIH, Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%
“…The triple transgenic mice gained significantly less body weight compared with nTg mice since 1‐month‐old ( P < .001, Figure 1A). Since our previous study have demonstrated that variations in tau expression levels did not affect the body weight in mice at different age stages, 20 these results suggest that α‐syn A53T mutation is the key gene that gives rise to a significant decrease in body weight in transgenic mice. In the rotarod test, compared to nTg mice, all triple transgenic mice exhibited significant impairment in motor coordination and balance from 2‐month‐old, while Pitx3‐A53T α‐Syn × Tau +/− mice seemed to perform worse than the other triple transgenic mice at 6‐month‐old (Figures 1B and S1A).…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, the pathways traced by all mice showed that Pitx3‐A53T α‐Syn × Tau −/− mice exhibited anxiety‐like behavior, as they spent significant shorter time in central zone during habituation compared with nTg mice (the ratio of time in central zone was 5.8% and 15.9%, respectively), while Tau −/− mice showed normal pathways compared with nTg mice (Figures 1E,F and S1B). Additionally, there were no obvious differences among Pitx3 × hTau , Tau +/− , Tau −/− , and nTg mice in the rotarod and open‐field tests (Figure S1), indicating that different expression levels of tau could not independently induce the motor abnormalities 20 . Taken together, these results suggested that tau deficiency could exacerbate movement impairment in the α‐syn A53T conditional transgenic mice.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations